Online product category and pricing strategies of land-based retailers: Homogenous vs prototypical orientation - Wu, Jin-Feng; Chang, Ya Ping; Yan, Jun; Hou, De-Lin (Internet research, 2019)
PurposeThe purpose of this paper is to understand how two online marketing orientations of land-based retailers in product category and price could change retail brand attitude when retail brand familiarities differ.Design/methodology/approachThis paper proposes a research model with two orientations in product category and price as antecedents of retail brand attitude change and retail brand familiarity as a moderator. Empirical data were collected from 684 shoppers across three land-based retailers to test the research hypotheses.FindingsBoth orientations in product category and price can improve customers’ retail brand attitudes. Retail brand familiarity plays a significant moderator in some of the situations. Online-offline product category congruence and online-prototypical price congruence have significantly positive effects on retail brand attitude change whether retail brand familiarity is high or low. The effect of online-offline price congruence is significant only among high-familiarity customers, while the effect of online-prototypical product category congruence is found to be significant only among low-familiarity customers.Research limitations/implicationsThe study identifies the moderating effects of retail brand familiarity on the relationships between two online marketing orientations in product category and price and retail brand attitude change. Based on the moderating effects, this study will help researchers to better understand the effectiveness of two online marketing orientations subject to varying degrees of retail brand familiarity in a multichannel retailing context.Practical implicationsThe findings of this study can guide land-based retailers to focus on the right orientations in product category and price to improve customers’ attitudes toward the retail brand when existing or new customers are targeted.Originality/valueThis study provides a first study to empirically assess the change in retail brand attitude prompted by homogenous and prototypical orientations in product category and price and subject to varying degrees of retail brand familiarity. Overall, the results offer insights of how land-based retailers could manage their overall performance by designing more effective online product category and pricing strategies for existing or new customers.